Spójność gospodarcza i społeczna postsocjalistycznych państw regionu Morza Bałtyckiego w świetle wybranych wskaźników - Kosiedowski, Wojciech (Economic and Social Cohesion of the Post-Soviet States of the Baltic Sea Region in the Light of Selected Indicators, 2007)
As a result of profound transformation undergone in 1990s, Post-Soviet Baltic States turned out to be in a similar geopolitic and economic position. Comparative analysis of statistical indicators shows that, having overcome some recessionary tendencies, which were typical for first stage of system transformation, Estonia, Latvia, Lithuania and Poland are realizing fast GDP growth, thanks to which they are reducing the distance between them and other EU Member States. During the existance of the so-called soviet camp, Baltic States were distinguished by the fact, that they kept certain market traditions alive. Undoubtedly, this circumstance helped in overcoming numerous difficulties and temporary slumps associated with market reforms. Entering the political and economic structures of the EU in a laborious but also consistent way, these states succeeded in reaching firm democracy and modern market system. Unlike the Commonwealth of Independent States, Baltic States were introducing market reforms in a very consistent manner, which enabled them to enter the path of dynamic developement. First lessons learned after the EU accession allow to assume that favourable development tendencies will also exist in the years to come.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 27-36